Does EVA truly reflect the performance of property companies in China? - Hui, Eddie C. M.; Gao, Yunzhi Orange; Chan, Ka Kwan Kevin (International Journal of Strategic Property Management, 2015)
This study investigates the economic value added (EVA) of 18 major Chinese property companies from 2006 to 2012. We categorize the companies in two ways: 1) companies concentrating on property vs multi-functional companies and 2) state-owned enterprises (SOEs) vs privately-owned enterprises (POEs). We find that on average, the mainland property companies experienced a negative EVA during the period 2006–2012. This is due to the companies undertaking long-term projects, and the companies do not recognize capital gain from property appreciation as income. Hence the EVA of the companies is, in fact, understated. The results also reveal that POEs outperform SOEs in terms of EVA. This reflects the inefficiency of SOEs. This research has two important implications to investors. Firstly, besides looking at the EVA of the companies, investors should also understand the nature of businesses of the companies thoroughly. Secondly, investors investing in emerging markets like China should have a thorough understanding of their market characteristics. This study can act as a reference for future studies in EVA of property companies in other emerging economies in the world. First Publish Online: 9 Oct 2015